The Effect of Transformational Leadership Style and Work Productivity on Employee Performance in The Mediation of Job Satisfaction - Rohmaniah, Rita; Amsar, Amsar; Ikut, Camilus Isidorus (Untag Business and Accounting Review, 2025)
This study aims to analyze the influence of transformational leadership style and work productivity on employee performance with job satisfaction as a mediating variable. The research sample consisted of 110 employees selected using the proportional sampling method. Data collection was carried out through a questionnaire with a Likert scale of 1-5, and data analysis used Structural Equation Modeling-Partial Least Square (SEM-PLS). The results of the study indicate that both transformational leadership style and work productivity have a positive and significant effect on employee performance. Furthermore, both of these factors also significantly increase job satisfaction. Job satisfaction itself plays a dual role: it directly improves employee performance and acts as a mediator. The result means that transformational leadership and high productivity don't just help performance directly; they also boost performance indirectly by making employees more satisfied with their roles.